Folic acid magnetic nanotheranostics for delivering doxorubicin: Toxicological and biocompatibility studies on Zebrafish embryo and larvae - Igartúa, Daniela (2018)
Doxorubicin (DOXO) is a chemotherapeutic agent widely used for the treatment of solid tumors and hematologic malignancies in both adults and children. However, DOXO causes short- and long-term cardiotoxicity and others undesirable side effects, such as nephrotoxicity and neurotoxicity. Magnetic nanoparticles (MNPs) allow the delivery of drugs specifically to target place, employing an external magnet. Moreover, they may act as contrast agents in MRI providing information on the diagnostic of diverse pathologies. In this way, two functions may be combined in a unique nanosystem known as theranostic. Also, the MNPs can be modified with folic acid (MNPs@FA) to increase the uptake by cancer cells that overexpress the FA receptors. In previous works, our collaborators obtained and characterized MNPs, MNPs@FA, and MNPs@FA@DOXO. It is essential to study the biosafety of nanotheranostic, and there is no published study of Fe 3 O 4 nanoparticles developmental toxicity. Because of that, this work aimed to study the in vivo toxicity and biocompatibility of DOXO, MNPs@FA, and MNPs@FA@DOXO using zebrafish embryo and larvae as an animal model. Viability, developmental toxicity, changes in spontaneous movement (neurotoxicity), changes in cardiac rhythm (cardiotoxicity), and efficiency of DOXO-uptake were studied. While the 48-h treatment with 50 μg/mL of DOXO resulted in a 30% larvae death and the development of significant morphological abnormalities, the treatment with MNPs@FA@DOXO and MNPs@FA did not reduce the viability and did not cause developmental abnormalities. Besides, the MNPs@FA@DOXO reduced the cardiotoxicity and promoted a more rapid and significant uptake of DOXO by zebrafish larvae.